Molecular structure similarity analysis using Tanimoto coefficient and its correlation analysis with Maltase-glucoamylase inhibitory activity of Nigella sativa’s compounds - Andayani, Nurita; Mulatsari, Esti (Journal of Natural Product for Degenerative Diseases, 2024)
Nigella sativa is one of the medicinal plants that are efficacious for treating diabetes mellitus. Diabetes mellitus is a chronic metabolic disorder characterized by hyperglycemia due to damage of insulin action, insulin production, and/or both. In this study, the molecular structure similarity analysis of the compounds in Nigella sativa to acarbose and the correlation analysis of the similarity with its activity as antidiabetic with the mechanism of maltase glucoamylase (MGAM) inhibition was carried out. Similarity analysis has been done used Tanimoto coefficient. The prediction of MGAM inhibitory activity has been done using molecular docking with molegro virtual docker. The Kaempferol 3-glucosyl-(1-2)-galactosyl-(1-2)-glucoside; (S)-2,3-Epoxysqualene; Quercetin 3-glucosyl-(1-2)-galactosyl-(1-2)-glucoside; Oleic Acid has activity as an inhibitor of MGAM with rerank score -107.8770, -102.1760, -95.7338, -92.4246 respectively and these has Tanimoto score 0.426, 0.319, 0.413, 0.357 respectively. The correlation analysis obtained that there is a significant relationship between the Tanimoto Coefficient and Rerank Score with the opposite relationship because the correlation value is negative. Greater the degree of molecular structure similarity of Nigella sativa’s compounds to acarbose more likely has the similar biological activity as MGAM inhibitory